Factors relevant to pre‐veliger nutrition of Tridacnidae giant clams. (12th August 2014) - Waters, Charles G.; Lindsay, Steve; Costello, Mark J.
Abstract: Tridacnid giant clams are of commercial interest for their nutritional, economic, and ecological significance throughout the Indo‐Pacific and Oceania. A major impediment to culturing tridacnid giant clams is larval mortality, typically >96%. The effects of suspended and particulate nutrients on tridacnid veliger development have been examined, but factors relevant to the nutritional condition of oocytes and trochophore larvae are unknown. This is significant because the nutritional transition from trochophore to veliger coincides with rises in larval mortality. Our review examines culture techniques known to enhance gamete viability of several marine viable bivalves of commercial interest, and critically assesses whether such methods are applicable to tridacnids in culture conditions. Techniques for optimizing the nutritional requirements of pre‐veliger tridacnids such as broodstock conditioning by supplemental feeding, monitoring the condition of oocytes ready for release, water temperature, egg attributes such as size and biochemical composition, and nutrient loads in culture water chemistry are examined. We include suggestions for optimizing nutritional conditions from gametogenesis through embryonic development, and conclude with a primer of research opportunities based on gaps in our understanding of tridacnid pre‐veliger nutrition compared with other bivalves. A major conclusion is that culture protocols should include pre‐veliger nutritional fitness as a critical factor in enhancing larval survival, growth and development.